Next Generation Molecular Diagnosis of Hereditary Spastic Paraplegias: An Italian Cross-Sectional Study - D'Amore, Angelica; Tessa, Alessandra; Casali, Carlo; Dotti, Maria Teresa; Filla, Alessandro; Silvestri, Gabriella; Antenora, Antonella; Astrea, Guja; Barghigiani, Melissa; Battini, Roberta; Battisti, Carla; Bruno, Irene; et al. (Frontiers in Neurology, 2018)
Hereditary spastic paraplegia (HSP) refers to a group of genetically heterogeneous neurodegenerative motor neuron disorders characterized by progressive age-dependent loss of corticospinal motor tract function, lower limb spasticity, and weakness. Recent clinical use of next generation sequencing (NGS) methodologies suggests that they facilitate the diagnostic approach to HSP, but the power of NGS as a first-tier diagnostic procedure is unclear. The larger-than-expected genetic heterogeneity — there are over 80 potential disease-associated genes — and frequent overlap with other clinical conditions affecting the motor system make a molecular diagnosis in HSP cumbersome and time consuming. In a single-center, cross-sectional study, spanning four years, 239 subjects with a clinical diagnosis of HSP underwent molecular screening of a large set of genes, using two different customized NGS panels. The latest version of our targeted sequencing panel (SpastiSure3.0) comprises 118 genes known to be associated with HSP. Using an in-house validated bioinformatics pipeline and several in silico tools to predict mutation pathogenicity, we obtained a positive diagnostic yield of 29% (70/239), whereas variants of unknown significance (VUS) were found in 86 patients (36%), and 83 cases remained unsolved. This study is among the largest screenings of consecutive HSP index cases enrolled in real-life clinical-diagnostic settings. Its results corroborate NGS as a modern, first-step procedure for molecular diagnosis of HSP. It also disclosed a significant number of new mutations in ultra-rare genes, expanding the clinical spectrum and genetic landscape of HSP, at least in Italy.